Opening a can of worms: unprecedented sympatric cryptic diversity within British lumbricid earthworms - KING, R. ANDREW; TIBBLE, AMY L; SYMONDSON, WILLIAM O.C (Molecular ecology, 2008)
Earthworms play a major role in many aspects of soil fertility, food web ecology and ecosystem functioning, and hence are frequently the subjects of, for example, ecological and toxicological research. Our aim was to examine the genetic structure of common earthworm species, to identify cryptic lineages or species that may be distinct ecotypes or biotypes (and hence confound current research based upon morphotypes) and to try to explain the massive cryptic diversity that eventually emerged. We demonstrated that species such as Allolobophora chlorotica, Aporrectodea longa, Aporrectodea rosea and Lumbricus rubellus all comprise highly divergent lineages with species-level divergence at the mitochondrial cytochrome oxidase I (COI) gene. In Allo. chlorotica alone, we found 55 haplotypes for COI, with 35 of these being found in pink and 20 in green morph worms. There were no cases of the two colour morphs sharing COI haplotypes. Phylogenetic analyses of mitochondrial COI and 16S genes showed the presence of five highly divergent lineages, suggesting the presence of multiple cryptic species within Allo. chlorotica. There was no clear geographical pattern to lineage distribution and many populations were polymorphic for both mitochondrial DNA lineage and colour morph. Amplified fragment length polymorphism results, based on two primer combinations, were broadly congruent with mitochondrial DNA results with one significant exception. Despite showing over 14% divergence at COI, amplified fragment length polymorphism markers showed that the two green morph lineages may be interbreeding and therefore represent a single taxon. The cryptic diversity revealed by these results has profound consequences for all areas of earthworm research.